Lung microbiome of chronic obstructive pulmonary disease patients with and without HIV infection in Pretoria, South Africa - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2021)
Thesis (PhD (Medical Microbiology))--University of Pretoria, 2020.